2015
DOI: 10.1021/acs.jctc.5b00402
|View full text |Cite
|
Sign up to set email alerts
|

Spin Doublet Point Defects in Graphenes: Predictions for ESR and NMR Spectral Parameters

Abstract: An adatom on a graphene surface may carry a magnetic moment causing spin-half paramagnetism. This theoretically predicted phenomenon has recently also been experimentally verified. The measurements of defect-induced magnetism are mainly based on magnetometric techniques where artifacts such as environmental magnetic impurities are hard to rule out. Spectroscopic methods such as electron spin resonance (ESR) and paramagnetic nuclear magnetic resonance (pNMR) are conventionally used in the development of magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Defects from more localized F vacancies were also explored including the two adjacent fluorine defects to produce an “ene” (ene­[2F]) or a four-fluorine vacancy to produce two adjacent “ene” defects (ene­[4F]). In this study no defects containing unpaired electrons (missing F or C) were considered, but paramagnetic point defects have previously been addressed by DFT methods . The calculated 19 F NMR spectra for the ene­[2F] and ene­[4F] defects are shown in Figure d,e.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Defects from more localized F vacancies were also explored including the two adjacent fluorine defects to produce an “ene” (ene­[2F]) or a four-fluorine vacancy to produce two adjacent “ene” defects (ene­[4F]). In this study no defects containing unpaired electrons (missing F or C) were considered, but paramagnetic point defects have previously been addressed by DFT methods . The calculated 19 F NMR spectra for the ene­[2F] and ene­[4F] defects are shown in Figure d,e.…”
Section: Results and Discussionmentioning
confidence: 99%
“…167 With this motivation, the characteristic spectroscopic parameters of the spin doublet point defects in graphene (ESR g-tensor and pNMR shielding tensor) were calculated by Vahakangas et al The authors considered the interactions of hydrogen and fluorine adatoms with graphene, graphane and fluorographene. 168…”
Section: Current State-of-the-art Methodologies Concerning the Magnet...mentioning
confidence: 99%
“…10,11 The basis set co2 is a completenessoptimized basis set 40 developed and tested for NSOR. 16 Additional benchmark tests against larger completeness-optimized basis sets 16,41 have shown that it provides a sufficient quality with modest computational effort (see Fig. S1 in ESI †).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a branch of spectroscopy related to NMR, known as nuclear magneto-optic spectroscopy (NMOS), has been explored both experimentally [4][5][6][7][8][9][10][11] and theoretically. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In contrast to classical NMR, which detects the signal through electromagnetic induction from the precessing nuclear magnetic moments, NMOS measures how these magnetic moments change the polarization state of the light passing through the sample. The interactions between the nuclei and the light, which are mediated by the electron cloud of the molecule, have shown promise for opening new types of spectroscopic measurements, such as observation of dipolar couplings in isotropic liquids 26 or mapping the properties of excited states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation